2014
DOI: 10.1007/s00441-014-1890-0
|View full text |Cite
|
Sign up to set email alerts
|

GFP-expressing S100β-positive cells of the rat anterior pituitary differentiate into hormone-producing cells

Abstract: Some non-endocrine cells in the pituitary anterior lobe are responsible for providing stem/progenitor cells to maintain hormone-producing cells. In particular, cells expressing S100β protein, a calcium-binding protein, have been hypothesized to be a pituitary cell resource. Accumulating data have revealed that S100β-positive cells comprise heterogeneous populations and some of them certainly show stem/progenitor characteristics in vivo. Hence, we examine whether S100β-positive cells have the capacity to differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 39 publications
2
20
0
Order By: Relevance
“…Estrogen-induced changes in S100β-immunofluorescent signal indicates a decreased signal in comparison to Orx middle-aged males (Figure 4). Our data, together with finding that FS cells coexpress S100β and SOX2, are in line with the assumption that a subpopulation of FS cells also serves a pool of SP cells [16,51,98]. SOX2 + / SOX9 + cells were reported to proliferate due to the effect of estradiol in vitro, with a predisposition to become lactotropic and luteinizing cells, with a small number differentiating into GH cells [49] (Figure 1).…”
Section: Effects Of Estradiol On Stem/progenitor Cells and Transdiffesupporting
confidence: 88%
See 2 more Smart Citations
“…Estrogen-induced changes in S100β-immunofluorescent signal indicates a decreased signal in comparison to Orx middle-aged males (Figure 4). Our data, together with finding that FS cells coexpress S100β and SOX2, are in line with the assumption that a subpopulation of FS cells also serves a pool of SP cells [16,51,98]. SOX2 + / SOX9 + cells were reported to proliferate due to the effect of estradiol in vitro, with a predisposition to become lactotropic and luteinizing cells, with a small number differentiating into GH cells [49] (Figure 1).…”
Section: Effects Of Estradiol On Stem/progenitor Cells and Transdiffesupporting
confidence: 88%
“…Estrogen may affect already-differentiated PRL cells, stem/progenitor cells, lineage-related cells and cells comprising the microenvironment. Transcriptional regulation of the following genes is mainly associated with tumorigenic action of estrogen in the pituitary: pituitary tumor transforming gene (PTTG); Myc; aldehyde dehydrogenase 1A1 (ALDH1A1); D2R, dopamine D2 receptor; mitogen-activated protein kinases (MAPK); vascular endothelial growth factor (VEGF); fibroblast growth factor 2 (FGF2); transforming growth factor β (TGFβ) and other growth factors and cytokines, such as ILs, interleukines [15,16,[40][41][42][43][44][45][46][47][48][49][50][51][52][53].…”
Section: Estrogen Signaling In the Anterior Pituitary And Prolactinommentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, S100β + -cells show multi-functions as phagocytes [ 31 ], supportive cells [ 22 ], cells forming a cell-network via gap junctions [ 32 ], and as cells regulating hormone release [ 33 ]. Notably, about 85% of S100β + -cells are composed of SOX2 + -cells in the adult rat pituitary [ 21 ], and some of them show an ability to differentiate into endocrine cells [ 34 ]. Therefore, a sub-population of S100β + -cells is regarded to be adult pituitary stem/progenitor cells.…”
Section: Pituitary Stem/progenitor Cells and Their Nichesmentioning
confidence: 99%
“…As postulated previously, some S100β-positive cells have the ability to differentiate into skeletal muscle cells [ 10 12 ]. More recently, we have reported that some S100β-positive cells are able to differentiate into all hormone-producing cell types in the anterior and intermediate lobes [ 13 ]. Despite these new findings, it is not yet clear how S100β-positive cells originate and develop into plural states with diverse roles.…”
Section: Introductionmentioning
confidence: 99%